Simulation Approach to Investigate the Influence of the Steering Wheel Angle And Vehicle Speed on the Rollover of a 4-Axle Truck Vehicle during Turning Maneuvers - Ta, Tuan Hung; Duong, Ngoc Khanh (Smart Systems and Devices, 2025)
The article aims to investigate the influence of vehicle speed and steering wheel angle on the rollover condition of a 4-axle truck vehicle. A 30-degree-of-freedom (DOF) dynamic model of a 4-axle truck is established using the Multibody System Method and the Newton-Euler equation system. The vehicle body is described with 6 DOFs. Additionally, 2 DOFs are used to describe the roll motion of the front and rear masses of the vehicle body, taking into account the influence of the torsional stiffness of the vehicle frame on vehicle dynamics. The Burckhardt tire model calculates the interaction forces between tires and the road, using experimental coefficients corresponding to the road with a maximum adhesion coefficient of 0.8. The simulation uses MATLAB-Simulink, with a 5 to 65 km/h speed range and a steering wheel rotation angle ranging from 25 to 300 degrees. The results have determined the vehicle rollover conditions based on the signs of the load transfer ratio of the axle and the entire vehicle. Together with the results of lateral acceleration, yaw rate, and roll angle of the vehicle. This result can be used to propose dynamic thresholds for designing early warning systems and anti-rollover control systems for multi-axle truck vehicles.